The Influence of Tourism Industry Agglomeration on Total Factor Productivity of Tourism Industry - Tan, Yuntao; Xu, Ming (Economics & Management Review, 2021)
This study selects the data of 30 provinces in China (excluding Hong Kong, Macao, Taiwan and Tibet) from 2008 to 2018 as samples, uses the DEA Malmquist index method to calculate the total factor productivity of tourism, and uses the location entropy method to measure the degree of tourism industry agglomeration. This paper analyzes the impact of tourism industry agglomeration on the development of tourism total factor productivity from two aspects of theoretical interpretation and empirical test. The main conclusions are as follows: Tourism industry agglomeration can signifcantly promote the improvement of tourism total factor productivity.